Cortisol Modulation by Ayahuasca in Patients With Treatment Resistant Depression and Healthy Controls - Galvão, Ana C. de Menezes; de Almeida, Raíssa N.; Silva, Erick A. dos Santos; Freire, Fúlvio A. M.; Palhano-Fontes, Fernanda; Onias, Heloisa; Arcoverde, Emerson; Maia-de-Oliveira, João P.; de Araújo, Dráulio B.; Lobão-Soares, Bruno; Galvão-Coelho, Nicole L. (Frontiers in Psychiatry, 2018)
Major depression is a highly prevalent mood disorder, affecting about 350 million people, and around 30% of the patients are resistant to currently available antidepressant medications. Recent evidence from a randomized controlled trial supports the rapid antidepressant effects of the psychedelic ayahuasca in treatment-resistant depression. The aim of this study was to explore the effect of ayahuasca on plasma cortisol and awakening salivary cortisol response, in the same group of treatment-resistant patients (MD) and in healthy volunteers (C). Subjects received a single dose of ayahuasca or placebo (dosing session), and both plasma and awakening salivary cortisol response were measured at baseline (before dosing session) and 48h after the dosing session. Baseline assessment (D0) showed blunted awakening salivary cortisol response and hypocortisolemia in patients, with respect to healthy controls. Salivary cortisol was also measured during dosing session, and we observed higher increases for both C and MD that ingested ayahuasca than placebo. After 48h from the dosing session with ayahuasca, patients’ awakening salivary cortisol response is similar to the ones detected in controls. No significant changes in plasma cortisol levels were observed 48 hours after the sessions. Therefore, these findings point to new evidence on the modulation of salivary cortisol levels as a result of an ayahuasca session, both in healthy and depressive volunteers. Considering that cortisol acts in regulation of distinct physiological pathways, emotional and cognitive processes, it is assumed to be critically involved to the etiology of depression and its regulation seems to be important for the treatment and remission of major depression, ayahuasca use as antidepressant should be further investigated. Moreover, this study highlights the importance of psychedelics in the treatment of human mental disorders.